Guideline for Survey, Investigation, and Design of Black Spot Location (SID-BSL) and Its Application in Lampung Province, Indonesia - Budi Hartanto Susilo (Institute of Research and Community Outreach - Petra Christian University, 2016)
In connection with the government's obligation to take responsibility for ensuring the safety of traffic and road transport for road users, it is necessary to conduct Surveys, Investigations, and Design of Black Spot Location (SID-BSL) to reduce traffic accident. Hence a guideline in conducting SID-BSL is needed. In this study, the author compiled a simple technique of prioritization for SID-BSL procedure and applies it to a research on National Roads in the Lampung Province. The technique of prioritization is simplified with four phase activities namely Preparation, Initial Analysis, Detail Survey, and Detail Analysis. The analysis technique is based on the ranking of Black Spot Locations using weighted accident number (WAN). Application procedure is applied on 237 events of accident on the National Roads in Lampung Province resulting five selected BSLs to be treated according to the availability of funds.